Conselho municipal de economia solidária: um estudo de uma política pública em São Carlos - Farah, André Misiuk (2019)
This research sought to analyze the experience of the Municipal Council of Solidarity Economy (COMESOL) of São Carlos-SP, regarding the exercise of citizenship, interpersonal relationships in the scope of cooperation and sociotechnical knowledge, aiming at the improvement of a public policy focused on social transformation. And to accompany its members, to identify the existence of singularities, that characterize their performance and the production of innovations, social technologies and political-methodological advances that can contribute to the articulation, management and control of the municipal public policy of Solidarity Economy. As a method, qualitative research was adopted with analysis of data from interviews, records in field notebooks and documents produced by COMESOL, to accompany the development of political practices that enable the approximation between popular sectors and the bureaucratic functioning of the State. The choice of this object has to do with the understanding of the relationship between government and civil society actors. For this, an analysis of the actions of the members of the Municipal Council of Solidarity Economy of São Carlos-SP was carried out, as well as semi-structured interviews with social actors and actresses involved, in order to verify how the advances achieved during its existence, with regard to the consolidation of social control, they may have contributed to effective changes in municipal public policies of Solidarity Economy. As a result, the dynamics of COMESOL and its functioning are presented, as well as the perception of the historical process of Solidarity Economy in the municipality, as well as of the technologies developed to assist in the development of the Council's work, introducing important elements for the continuity of the advancement of municipal public policy of Solidarity Economy of São Carlos.